(untitled) (Development Service Industry Management, 2024)
The article discusses the imperatives, principles and criteria of environmental policy in Ukraine. Integrated, evolutionary and practice-oriented approaches, comparative studies, methods of analysis and synthesis are chosen as the methodology of the article. The key elements of Ukraine’s environmental policy are considered, which include: protection of natural resources, biosphere and ecosystem; reduction of pollution; fulfillment of tasks to reduce emissions into the atmosphere; minimization of pollution of water and soil resources; energy efficiency and exploitation of energy supply technology in the strategy of increasing the income of energy enterprises; implementation of strategic plans in accordance with the needs of future generations; minimization of negative effects on the environment; cooperation of interested organizations. On a global scale, the relevance of environmental management is growing. International environmental policy has been carried out since the 1970s of the 20th century in order to eliminate the problems of environmental pollution and optimize the methodology of monitoring the ecosystem. World practice has put forward effective methods for evaluating the environmental strategy and evaluating the level of environmental pollution taking into account the «PIGU» tax per unit of the organization’s products, which compensates for the negative external impact, and taking into account the tools of economic analysis. Ukrainian directives were not studied in international approaches to the assessment of ecological development, and no measures were taken for international implementation. Lawmakers in Ukraine are discussing the problem of the environmental law system, the regulations of which contain certain regulatory and legal documents. Ukraine’s environmental policy is based on regulatory and economic imperatives, principles and approaches. In order to reform the environmental legislation of Ukraine, it is necessary to solve a number of organizational and legal tasks. The global practice of ecopolitics uses legal instruments on the basis of the «polluter pays» principle, and financial resources for reducing emissions are implemented on a large scale in the context of global economic policy. The World Organization for Economic Co-operation and Development promotes the development of the economy, overcoming poverty, and adheres to the principle of creating values of the organization, such as the observance of democratic norms and open regulation of trade in the global financial system. The experience of the UN makes it possible to effectively implement normative instruments in Ukraine’s ecopolitics. It was concluded that the environmental policy of Ukraine, based on a regulatory approach, prohibits the use of hazardous substances, aims to reduce emissions of garbage accumulations, entails fines and sanctions, and determines the rights and obligations of nature users. In the international comparison, attention is paid to environmental imperatives, principles and criteria; regulatory and economic requirements of sustainable development; and the improvement of regulations, standards and norms. The normative approach becomes a tool for the real implementation of Ukrainian legislation. It is concluded that the range of regulatory and economic instruments formulates the conceptual basis for the implementation of Ukraine’s environmental policy. Ecopolitics of Ukraine is based on regulatory and economic imperatives, principles and criteria. In order to improve Ukraine’s ecopolitics, a whole spectrum of legal and organizational tasks must be solved.